The spatial impacts of informal land use and interpreting the conformity of informal settlement growth with an adopted land use plan: the case of Burayu City, Ethiopia - Bayuma, Tefera Beyera (Frontiers in Built Environment, 2025)
Conformity with land-use planning in a city is problematic in informal settlement areas and requires the interpretation of the reasons for informal land use. This study aimed to evaluate the spatial impact of informal land use on planning, determine the extent to which such informal land use conforms with land-use plans, and the reasons for this. This study applied a case study with both a qualitative and quantitative research approach in which the quantitative spatial data in this study were explained and contextualized by qualitative data. Primary data were collected by interviews with eight informal settlers and twelve experts. The secondary data included are the proposed land-use map and the city’s parcel-based informal land-use inventory types. The findings revealed that 81% of informal houses occupied parcels of land larger than 140 m2 due to demand for larger plot sizes. This led to a shortage of space for service provision. This study also found that 69.10% of informal land-use types adhered to the land-use plans. This is due to the administrator’s conscious decision to include informal land use into the city’s structural plan and the deliberate efforts of informal settlers to be part of the structural plan by obtaining information from city planners. This implies that the behavior of government and individual actors can lead informal land-use types to conform with the adopted plan.